HUBUNGAN SIKAP HIDUP SEHAT DAN PENGETAHUAN TENTANG COVID 19 TERHADAP PERILAKU AMAN PADA SAAT PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) TRANSISI - Charles Situmorang; Adam Zulkifli (JURNAL TECHLINK, 2021)
In early 2020 the whole world was shocked by the Coronavirus, which spreads so fast, almost the entire world is infected. Coronavirus is an RNA virus with a particle size of 120- 160 nm. This virus mainly infects animals, including bats and camels. This virus not only attacks the health side but attacks the world economic side, so the Indonesian government immediately makes a policy by implementing a transitional PSBB which is expected to coexist with the community with this virus on condition that they always adhere to health protocols. This study aims to find a relationship between healthy living and safe behavior and to find a relationship between knowledge about Covid 19 and safe behavior. This study uses a questionnaire method to obtain data in the field by distributing a google form link to willing respondents. For data analysis, this research uses the homogeneity test method, correlation test, and regression test. Based on the results of the study, it was found that between a healthy lifestyle and safe behavior, a correlation significance value of 0.663 was obtained where this value was more than 0.5 which indicated there was no relationship and between knowledge about Covid 19 and safe behavior, the correlation significance value was 0.890 where this value more than 0.5 which indicates there is no relationship.